Response of the mechanical and chiral character of ethane to ultra‐fast laser pulses - Mi, Xiao Peng; Lu, Hui; Xu, Tianlv; Früchtl, Herbert; Mourik, Tanja; Paterson, Martin J.; Kirk, Steven R.; Jenkins, Samantha (Journal of computational chemistry, 2024)
A pair of simulated left and right circularly polarized ultra‐fast laser pulses of duration 20 femtoseconds that induce a mixture of excited states are applied to ethane. The response of the electron dynamics is investigated within the next generation quantum theory of atoms in molecules (NG‐QTAIM) using third‐generation eigenvector‐trajectories which are introduced in this work. This enables an analysis of the mechanical and chiral properties of the electron dynamics of ethane without needing to subject the C‐C bond to external torsions as was the case for second‐generation eigenvector‐trajectories. The mechanical properties, in particular, the bond‐flexing and bond‐torsion were found to increase depending on the plane of the applied laser pulses. The bond‐flexing and bond‐torsion, depending on the plane of polarization, increases or decreases after the laser pulses are switched off. This is explainable in terms of directionally‐dependent effects of the long‐lasting superpositions of excited states. The chiral properties correspond to the ethane molecule being classified as formally achiral consistent with previous NG‐QTAIM investigations. Future planned investigations using ultra‐fast circularly polarized lasers are briefly discussed. The ethane C1‐C2 bond critical point (BCP) Hessian of ρ(r) eigenvector‐trajectories T(s) for the for the clockwise (CW, [+1]) (red) and counter‐clockwise (CCW, [−1]) (blue) circularly laser pulse polarized in yz plane 60 femtoseconds after the pulses are switched off. The end of each T(s) is denoted by a cube marker. The most (±e2) and least (±e1) preferred eigenvector directions of the total charge density accumulation ρ(rb). The inset is the view down the ethane C1‐C2 BCP bond‐path, showing the Cartesian yz axes, where the BCPs are represented by undecorated green spheres.